2019
DOI: 10.1007/s00787-019-01342-4
|View full text |Cite
|
Sign up to set email alerts
|

Emotional disorder and absence from school: findings from the 2004 British Child and Adolescent Mental Health Survey

Abstract: Emotional disorder may be associated with absence from school, but the existing evidence is methodologically weak. We studied the relationships between anxiety, depression and emotional difficulties, and school absence (total, authorised and unauthorised) using data from the 2004 British Child and Adolescent Mental Health Survey (BCAMHS). The BCAMHS was a cross-sectional, community survey of 7977 5-to 16-year-olds. Emotional disorder was assessed using the Development and Wellbeing Assessment (DAWBA), and emot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 48 publications
12
40
0
Order By: Relevance
“…Our finding that students who had been truanting showed decreased mental HRQOL is in agreement with previous reviews and studies on the association between unexcused absence and depression or anxiety [37,38,39,40]. The association between higher physical HRQOL and truancy might be explained within previous research where five out-of-school activity portfolios were identified.…”
Section: Discussionsupporting
confidence: 92%
“…Our finding that students who had been truanting showed decreased mental HRQOL is in agreement with previous reviews and studies on the association between unexcused absence and depression or anxiety [37,38,39,40]. The association between higher physical HRQOL and truancy might be explained within previous research where five out-of-school activity portfolios were identified.…”
Section: Discussionsupporting
confidence: 92%
“…A similar pattern of reverse causation could apply to the links between academic attainment and depression, i.e., emerging depressive symptoms could negatively affect the young person's motivation to engage with education or even impair their memory or executive functions. It has also been shown that depression is associated with poorer school attendance in adolescence [10]. Countering this argument, the prospective relationships between childhood ADHD and late adolescent depression still held when controlling for emotional problems at age 8 or depressive symptoms at age 14, suggesting that depression did not precede the peer problems or academic difficulties observed in this study.…”
supporting
confidence: 49%
“…This may be due to the fact students with high scores on school refusal, based on the first three SRAS-R factors, have also been associated with internalizing behaviors. In other words, they display manifestations of anxious and depressive behavior ( Evren et al, 2015 ; Finning et al, 2019 ; Knollmann et al, 2019 ; Lawrence et al, 2019 ; Fornander and Kearney, 2020 ). These behaviors, characterized by a low emotional control, may lead to the manifestation of aggressive behavior as a means of escape ( Henry et al, 2012 ; Bucur et al, 2020 ; Fernández-Sogorb et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%